Complexo de uso misto quadra Viva - Guarnieri, Luessa Daniela (My University, 2020)
The present work has as main objective to present in a summarized way the development of the Architectural project of a Mixed Use complex in the city of Garibaldi, Rio Grande do Sul. With this, the purpose is to generate a better use of a partially underutilized block in the center the urban center of the city in question. The Mixed Use Complex named Quadra Viva, brings in its conception different uses such as housing, commerce, services and passive leisure areas. The project brings to the city a more integrated and simple way of living and undertaking with minimal housing and commercial rooms of various sizes and easy to rent. [resumo fornecido pelo autor]
O presente trabalho tem como objetivo principal apresentar de forma resumida o desenvolvimento do projeto Arquitetônico de um complexo de Uso Misto na cidade de Garibaldi, Rio Grande do Sul. Com este, o propósito, é gerar uma melhor utilização de um quarteirão parcialmente subutilizado no miolo do centro urbano da cidade em questão. O Complexo de Uso Misto nomeado Quadra Viva, traz em sua concepção diferentes usos como habitação, comércio, serviços e áreas de lazer passivo. O projeto traz para cidade uma forma mais integrada e simples de morar e empreender com habitações mínimas e salas comerciais de diversos tamanhos e de fácil locação. [resumo fornecido pelo autor]
Keywords: Projeto arquitetônico; Arquitetura